Congenital corrected transposition of great arteries with situs solitus, dextrocardia and pulmonary stenosis - Kumar, Ansul; Kalra, Sanjay; Padhy, Ajit; Gupta, Vijay K. (International Surgery Journal, 2016)
A 12 years female presented with dyspnea on exertion. NYHA class-II for last 3 years with reduced effort tolerance and cyanosis since child hood was reported. On examination apex in 5th intercostal space was shifted to the right of mid clavicular line, first heart sound was single (S1), the pulmonary component of second heart sound was loud (P2). Grade 3/6 pan systolic murmur over right parasternal area was present. Chest X-ray, echocardiogram, CT cardiac angiography and cardiac catheterization affirmed situs solitus, dextrocardia, CCTGA with valvular and infundibular pulmonary stenosis, bilateral superior venacavae, large subaortic ventricular septal defect (VSD) with left sided aortic arch and normal biventricular function (Figure 1and 2).